(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
This article addresses the problem of developing leadership qualities in future reserve officers as a necessary condition for forming their managerial competence. Leadership is viewed as a complex psychological and pedagogical phenomenon that differs from traditional commanding qualities. The authors’ focus revolves around the factors that contribute to the fostering leadership qualities in future reserve officers of Ukraine during their training in military educational institutions or academies (MEI) of Ukraine and military training departments of higher education institutions (MTD HEI). Furthermore, the body of the article goes on to discuss the role of leadership qualities in shaping the managerial competence of Ukrainian citizens studying in the reserve officer training program. The issue of enhancing the quality of professional characteristics and the role of the teaching staff of military training departments (faculties) is discussed, taking into account their combat experience and pedagogical skills. The authors highlight the essential thesis that modern military training requires new approaches aimed at developing leadership qualities in military academy cadets, which facilitates their successful management of units. The article explores the contradictions between traditional officer training methods and contemporary leadership requirements. The key components of managerial competence are delineated as motivational, cognitive, functional, and personal dimensions, with particular emphasis placed on the necessity of cultivating skills for self-management, as well as for effectively leading subordinates and teams. It is worth noting that the significance of physical preparedness for officers is underscored, as it contributes to their authority and credibility among subordinates. To recapitulate the core of the aforementioned, it could be stated that an officer, in their capacity as a leader, bears the responsibility for upholding statutory interpersonal relationships within the military unit as a cohesive combat entity. Concurrently, the officer must adeptly manage the informal dynamics among subordinate soldiers, considering their individual psychological and physical attributes. The overarching objective of such a responsible role is to ensure the efficiency and effectiveness of the subordinate unit in executing routine training and combat assignments related to military service.